Advanced Topics in Control Systems Theory Lecture Notes from FAP 2004 - Lamnabhi-Lagarrigue, Françoise; Loría Perez, Julio Antonio; Viatcheslavovna Panteley, Elena (Lecture Notes in Control and Information Sciences, 2005)
"Advanced Topics in Control Systems Theory" contains selected contributions written by lecturers at the second (annual) Formation d'Automatique de Paris (FAP) (Graduate Control School in Paris). It is addressed to graduate students and researchers in control theory with topics touching on a variety of areas of interest to the control community such as cascaded systems, flatness, optimal control, and Hamiltonian and infinite-dimensional systems. The reader is provided with a well-integrated synthesis of the latest thinking in these subjects without the need for an exhaustive literature review. "Advanced Topics in Control Systems Theory" can be used to support either a one-term general advanced course on nonlinear control theory, devoting a few lectures to each chapter, or for more focused and intensive courses at graduate level. The book's concise but pedagogical manner will give an ideal start to researchers wishing to broaden their knowledge in aspects of modern control theory outside their own expertise.